Raz jeszcze o siedzibach dworskich w Wojsławicach - Kajzer, Leszek (Biuletyn Szadkowski, 2011)
Wojsławice manor is generally considered to be one of the most interesting historical sites of this kind in the region of Szadek. In addition to the fortified 16th century mansion called “small castle”, about which J. Agustyniak wrote in the tenth volume of Biuletyn Szadkowski, at least two interesting residential buildings can be found there. One of them is a manor house dating from the first half of the 19th century, mediumsized with some features of Classicism. The main object on this estate is a brick, onestorey palace built around 1900. All residential buildings and the old park are associated with Siemiatkowscy family, who lived in Wojsławice for seven generations.